Introducing Preservice Science Teachers to Computer Science Concepts and Instruction Using Pseudocode - Brauer, Kayla; Kruse, Jerrid; Lauer, David (Innovations in Science Teacher Education, 2020)
Preservice science teachers are often asked to teach STEM content. While coding is one of the more popular aspects of the technology portion of STEM, many preservice science teachers are not prepared to authentically engage students in this content due to their lack of experience with coding. In an effort to remedy this situation, this article outlines an activity we developed to introduce preservice science teachers to computer science concepts such as pseudocode, looping, algorithms, conditional statements, problem decomposition, and debugging. The activity and discussion also support preservice teachers in developing pedagogical acumen for engaging K-12 students with computer science concepts. Examples of preservice science teachers’ work illustrate their engagement and struggles with the ideas and anecdotes provide insight into how the preservice science teachers practiced teaching computer science concepts with 6th grade science students. Explicit connections to the Next Generation Science Standards are made to illustrate how computer science lessons within a STEM course might be used to meet Engineering, Technology, and Application of Science standards within the NGSS.